An Exploration of the Benefits of an Animallike Robot Companion with More Advanced Touch Interaction Capabilities for Dementia Care - Jung, Merel M.; van der Leij, Lisa; Kelders, Saskia M. (Frontiers in ICT, 2017)
Animallike robot companions such as robotic seal Paro are increasingly used in dementia care due to the positive effects that interaction with these robots can have on the well-being of these patients. Touch is one of the most important interaction modalities for patients with dementia and can be a natural way to interact with animallike robots. To advance the development of animallike robots we explored in what ways people with dementia could benefit from interaction with an animallike robot with more advanced touch recognition capabilities and which touch gestures would be important in their interaction with Paro. In addition we explored which other target groups might benefit from interaction with animallike robots with more advanced interaction capabilties. In this study we administered a questionnaire and conducted interviews with two groups of health care providers who all worked in a geriatric psychiatry department. One group used Paro in their work (i.e., the expert group; $n=5$) while the other group had no experience with the use of animallike robot (i.e., the layman group; $n=4$). The results showed that health care providers perceived Paro as an effective intervention to improve the well-being of people with dementia. Examples of usages for Paro that were mentioned were providing distraction, interrupting problematic behaviors and stimulating communication. Furthermore, the care providers indicated that people with dementia (would) use mostly positive forms of touch and speech to interact with Paro. Paro's auditory responses were criticized because they can overstimulate the patients. Additionally, the care providers argued that social interactions with Paro are currently limited and therefore the robot does not meet the needs of a broader audience such as healthy elderly people that still live in their own homes. The development of robot pets with more advanced social capabilities such as touch and speech recognition might result in more intelligent interactions which could help to better adapt to the needs of people with dementia and could make interactions more interesting for a broader audience. Moreover, the robot's response modalities and its appearance should match the needs of to the target group.